Pengembangan Media Pembelajaran Interaktif Berbasis Website untuk Meningkatkan Kemampuan Berpikir Kritis dan Literasi Kesehatan Siswa pada Materi Sistem Pertahanan Tubuh Kelas XI SMA - Delvita; Evy Yulianti; Dzikry Arrahim (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop website-based learning media on the body's defense system and test interactive learning media's feasibility, practicality, and effectiveness to improve students' critical thinking skills. They used the ADDIE model (analysis, design, development, implementation, and evaluation). The trial of interactive learning media based on the body's defense system website was conducted using a pseudo-experimental research method using a non-equivalent pretest-posttest control design. The number of field trial subjects was 60 students from class XI MIPA SMA Negeri 1 Cangkringan, consisting of 30 experimental class students and 30 control class students. The data sampling technique used a critical thinking skills test questionnaire. The effect of website interactive learning media on essential thinking skills was measured using SPSS 26 with t-test, effect size, and correlation test. The results showed that the website-based interactive learning media is feasible and practical for teachers and students. This media is efficacious in improving students' critical thinking skills.